TB Control in Humans and Animals in South Africa: A Perspective on Problems and Successes - Meiring, Christina; van Helden, Paul D.; Goosen, Wynand J. (Frontiers in Veterinary Science, 2018)
Mycobacterium tuberculosis (M. tb) remains one of the most globally serious infectious agents for human morbidity and mortality, but with significant differences in prevalence across the globe. In many countries, the incidence is now low and declining, but control and eradication remain a distant view. Similarly, the prevalence of bovine TB caused by Mycobacterium bovis (M. bovis), varies significantly across regions, although unlike for M. tuberculosis, data are sparse. The reduction in incidence and prevalence and control of both human and bovine TB is difficult and costly, yet some countries have managed to do this with some success. This perspective will consider some of the critical control steps we now know to be important for the control of TB from M. tuberculosis in humans living in South Africa, where the incidence of TB is the highest currently experienced. Despite the high incidence of human TB, South Africa has been able to reduce this incidence remarkably in the past few years, despite limited resources and high HIV prevalence. We draw from our experience to ascertain whether we may learn useful lessons from control efforts for both diseases in order to suggest effective control measures for bovine TB.